Innovative solutions of improving efficiency in public management - V. Onyshchuk, Svitlana (2020)
The paper reflects the analyzing of current trends in the use of innovation, technical and technological potential of different countries in the context of optimizing the interaction of government and the public to stimulate the effectiveness of public management. As a result of correlation analysis, it has been proven that the basic factors, determining the effectiveness of the outlined management model, are the level of development of online services and the availability of the necessary information data infrastructure. Perspective for e-government lies in the ability to improve and adapt innovative tools to public management systems around the world by using the existing digital, research and technological potential of governments of different countries.